Nisan Plakpling, Tipe Nisan Peralihan dari Pra- Islam ke Islam - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2007)
AbstractThe plakpling gravestone type spreaded a lot in Aceh, which is quiet possible that it’s a change of type from pre Islam to Islam era. From the inscriptions on it’s surface, this gravestone was assumed that it’s older than other gravestones.